Cytotoxic and apoptogenic effect of hypericin, the bioactive component of Hypericum perforatum on the MCF-7 human breast cancer cell line. Issue 1 (December 2015) - Mirmalek, Seyed; Azizi, Mohammad; Jangholi, Ehsan; Yadollah-Damavandi, Soheila; Javidi, Mohammad; Parsa, Yekta; Parsa, Tina; Salimi-Tabatabaee, Seyed; Ghasemzadeh kolagar, Hossein; Alizadeh-Navaei, Reza
Abstract Background Breast cancer is the most prevalent malignancies among the women that have a high mortality. Previous studies demonstrated that hypericin, a bioactive component ofHypericum perforatum have a cytotoxic effect on the malignant cell lines. However, an anti-carcinogenic activity of hypericin on MCF-7 is uncertain. To investigate the cytotoxic effect of hypericin on MCF-7 cells, a human breast adenocarcinoma cell-line, that resistance to chemotherapy. Methods The MCF-7 and fibroblast (as normal cell line) were treated with various concentrations of hypericin, and Cisplatin as a positive control for 24 and 48 h. Cytotoxicity activity was measured and confirmed by MTT assay and Trypan blue staining, respectively. In addition, Apoptosis were determined by Annexin V/Propidium Iodide assay. Immunocytochemistry (ICC) analysis for bcl2 and p53 proteins performed to further investigate different expression of these genes in different samples. Results Both cisplatin and the hypericin exhibited a dose-dependent cytotoxic effect in the MCF-7 cell line. Although the LD50 of the hypericin was significantly lower when compared to cispaltin (5 vs. 20 μg/ml), it continued to decrease the growth rate of the MCF-7 cells when tested at higher concentration than LD50. In contrast, cisplatine, at higher concentration than LD50, completely inhibited the growth of the MCF-7 in 48 h. Regarding Annexin V/Propidium results, treatment of MCF-7 cells with LD50 concentration of cisplatin and hypericin showed 60 and 52 % apoptosis in 24 h, respectively. ICC analysis for bcl2 and p53 also confirmed our results; in treated samples for the dose of LD50 in 24 and 48 h of cisplatin and hypercin, more cells expressed p53 (guardian of cells in front of tumor formation/progression) and less expressed bcl2 (which has anti apoptotic activity) compared to untreated samples. Conclusions Considering that hypericin showed to be cytotoxic, it seems to be a chemopreventive agent and a good candidate for antineoplastic drug development.